2020
DOI: 10.3389/fpubh.2020.00225
|View full text |Cite
|
Sign up to set email alerts
|

Genital Micro-Organisms in Pregnancy

Abstract: The microbiome of the female genital tract may undergo changes in pregnancy due to metabolic, endocrinological, and immunological alterations. These dysbiotic states may cause infections which may ascend upwards to the feto-placental unit or may be seeded hematogenously. These low grade and often low virulent infectious states lead to chronic inflammatory states and maybe associated with adverse maternal and neonatal outcome. Organisms have been isolated from amniotic fluid and placentae from women delivering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 89 publications
(121 reference statements)
0
18
0
3
Order By: Relevance
“…were the dominant colonizers in reproductive sites [ 38 ] and defended these sites against abnormal or pathogenic microorganisms [ 61 ]. Accordingly, more probiotic interventional studies have been conducted on reproductive failures with lactobacilli imbalance, such as adverse pregnancy outcomes [ 16 ], a significant decrease in endometrial implantation [ 36 ], and altered IVF outcomes [ 62 , 63 ]. The Lactobacillus genus has optimal probiotic properties, including high hydrophobicity and self-regulation, adhesion to epithelial cells and acid production [ 64 ], and restoration of healthy urogenital microbiota [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…were the dominant colonizers in reproductive sites [ 38 ] and defended these sites against abnormal or pathogenic microorganisms [ 61 ]. Accordingly, more probiotic interventional studies have been conducted on reproductive failures with lactobacilli imbalance, such as adverse pregnancy outcomes [ 16 ], a significant decrease in endometrial implantation [ 36 ], and altered IVF outcomes [ 62 , 63 ]. The Lactobacillus genus has optimal probiotic properties, including high hydrophobicity and self-regulation, adhesion to epithelial cells and acid production [ 64 ], and restoration of healthy urogenital microbiota [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the human microbiome with the application of this method have definitely shown more richness in the microbiota (both aerobic and anaerobic) than those identified using culturing methods [ 12 ]. For this reason, the implementation of the NGS seems to be an appropriate method to monitor the changes in the vaginal composition of bacteria during pregnancy and its relationship with susceptibility to infection, the possibility of premature birth, and postpartum complications [ 3 , 6 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, changes in microbial communities which are potentially associated with disease can be studied. A dysbiotic vaginal environment, like the one observed in bacterial vaginosis (BV), is interlinked with an augmented risk of contracting STIs [109] and adverse pregnancy outcomes [6].…”
Section: The New Possibilities Of-omicsmentioning
confidence: 99%
“…The two most common bacterial STIs, CT and NG, not only cause pelvic inflammatory disease and chronic pelvic pain in women, but also result in ectopic pregnancies and miscarriages, preterm labor, increased risk of mother-to-child HIV transmission, conjunctivitis, and pneumonia in neonates [5]. Although the evidence is inconclusive, MG and TV infection in pregnancy have also been associated with preterm birth [6]. Neonates can become infected with HSV at birth from an infected mother, with potential involvement of the central nervous system and fatal consequences [7].…”
Section: Introductionmentioning
confidence: 99%